2009
DOI: 10.1038/nn.2334
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase is the primary source of superoxide induced by NMDA receptor activation

Abstract: Neuronal NMDA receptor (NMDAR) activation leads to the formation of superoxide, which normally acts in cell signaling. With extensive NMDAR activation, the resulting superoxide production leads to neuronal death. It is widely held that NMDA-induced superoxide production originates from the mitochondria, but definitive evidence for this is lacking. We evaluated the role of the cytoplasmic enzyme NADPH oxidase in NMDA-induced superoxide production. Neurons in culture and in mouse hippocampus responded to NMDA wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
472
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 489 publications
(495 citation statements)
references
References 49 publications
(86 reference statements)
19
472
1
3
Order By: Relevance
“…This finding supplements recent reports indicating that NOX activation links NMDA-receptor-mediated increases in (Ca) i levels and ROS formation. 7 Our data now suggest that NOX activity is also involved in glutamate-induced ROS formation and cell death in the absence of NMDA receptors and independent of increased (Ca) i .…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…This finding supplements recent reports indicating that NOX activation links NMDA-receptor-mediated increases in (Ca) i levels and ROS formation. 7 Our data now suggest that NOX activity is also involved in glutamate-induced ROS formation and cell death in the absence of NMDA receptors and independent of increased (Ca) i .…”
Section: Discussionmentioning
confidence: 50%
“…Prominent sources of physiological intracellular ROS formation that may further be stimulated under conditions of cellular stress are, for example, lipoxygenases (LOXs), cyclooxygenases (COXs), NADPH-oxidases (NOXs) and the uncoupled mitochondrial respiratory chain. 7,8 After exposure to glutamate, dysfunctional mitochondria may generate toxic amounts of intracellular ROS, which may further severely perturb cellular redox balance. 9 In addition, these organelles host pro-apoptotic proteins, for example, apoptosis-inducing factor (AIF), cytochrome c or SMAC/ DIABLO (second mitochondria-derived activator of caspase/ direct IAP binding protein with low pI), which may trigger caspase-dependent or caspase-independent death when released into the cytosol.…”
mentioning
confidence: 99%
“…N-methyl-D-aspartate (NMDA) receptors (NMDARs)] by glutamate triggers several signal processes, such as calcium influx, activation of nitric oxide (NO) synthase, and superoxide formation (Chetkovich et al, 1991;Lafon-Cazal et al, 1993). Following neuronal NMDAR activation, the increased NADPH oxidase activity can be the key source of superoxide (O 2 · -) production (Brennan et al, 2009;Bókkon and Antal, 2011;Tsai et al, 2012). In addition, initial superoxide signals produced by the NADPH oxidase can stimulate secondary mitochondrial superoxide and various ROS production.…”
Section: Phosphene Generation In the Visual Cortex By Means Of Excessmentioning
confidence: 99%
“…The autoantibody reaction to the NMDA receptor (NR2A) 24,25 is a humoral immune reaction. Dambinova et al 26 measured NR2A antibody levels in serial order within the first 72 hours, found that the peak of increase was at the first 10 to 12 hours after ischemic cerebral vascular attack.…”
Section: Discussionmentioning
confidence: 99%